RESULTS OF THE IMMUNIZATION ACCORDING TO THE NATIONAL CALENDAR ASSOCIATED WITH VACCINATION AGAINST INFLUENZA IN CHILDREN WITH SOMATIC DISORDERS AND IMMUNODEFICIENCY - S. M. Kharit; A. A. Ruleva; O. V. Goleva; O. S. Kalinogorskaya; V. A. Apryatina (Вопросы современной педиатрии, 2014)
Aim: to study safety and immunological efficacy of vaccination against influenza in separate and associated immunization according to the National Calendar. Patients and methods: 100 children with various disorders as well as children with HIV subjected to revaccination against diphtheria, tetanus, measles, parotiditis and rubella, were included into the study. Children were divided into 5 groups of 20 persons each: groups of separate or associated vaccination. In order to assess safety of vaccination children were observed for 30 days after vaccination. In order to analyze immunologic efficacy participants were taken serum tests before and on the 30th day after vaccination. Results: the study demonstrated high safety of the vaccine against influenza. Mild and moderate topical and general reactions were observed in isolated instances and did not differ in comparison groups. Simultaneous vaccination against influenza with immunization against diphtheria, parotiditis and rubella did not influence synthesis of antibodies, while synthesis of antibodies against measles was decreased; immunization against diphtheria and measles when associated with vaccination against influenza depressed synthesis of antibodies against A/H3N2 influenza. Conclusions: vaccine against influenza has low reactivity, high safety and can be used in association with immunization according to the National calendar in independence to somatic disorders of patients.